CENOZOIC TECTONIC ACTIVITIES IN RED RIVER BASIN AND ANDJACENT AREA - Phach, Phung Van; Chinh, Vu Van (Vietnam Journal of Marine Science and Technology, 2007)
Using cornbinarion of geomorphologic, topographic, remote sensed images, structural features and tectonophysic analysis we have deterrnined 4 principle tectonic phases in Red River Cenozoic Basin and adjacent area  as follow (in the order from ancient to recent). The first tectonic phase was characterized by east - west extension. It can be remarked in many places of Ninh  Binh  province, in particular within Dong Giao limestone forrnation (T2 a dg), with numerous of large  sub-longitudinal extensional cracks, filled up by calcite up to meters in thickness. The event can be related to  one of the dextral strike slip of Red River fault zone and had participated in the earliest rift - forming process of region. The second tectonic phase had rnainly strike slip nature, with east-west cornpression, that marked as well by  cessation of regional rift - forming process in the region (the unconformity of 32-30 M.y.BP), as by onset of Cenozoic oceanic crust spreding of Eastern Vietnam Sea and by sinistral strike - slip of Red River Fault. The third tectonic phase, with maximum NE - SW compression, has caused some significant thrust activities along coastal zone and has stimulated an inverse uplift - shortening in NW part of Red River Basin in the Early - Midle Miocene, with the unconfornities 15.5 and 5.5 M.y.BP. The most recent tectonic phase that is revealed in study area by very recent NE - SW extensions, that creates  a numerous of narrow valleys of NW - SE orientation and causes a dextral and a sinistral movements of sub-latitudinal and sub-longitudinal accordingly. This extension can be considered as accompany of intensive  extension-subsidence in Red River basin, that contents of 4 km Pliocene - Quaternary sediment in the center.